Dynamics of Concatenation between Cardiac Output and Indices of Arterial Blood Presure during Graded Exercise Stress in Endurance Cohort - Vilma Papievienė; Eugenijus Trinkūnas; Alfonsas Buliuolis; Albinas Grūnovas; Jonas Poderys (Lithuanian Sports University, 2018)
Research background and hypothesis. Potential mechanisms through which muscle perfusion is altered during prolonged exercise are not fully understood. The methods applied in the  analysis of human data are very important   because  many crucial variables are not directly measureble or even identifiable. Research aim  was to  find out the peculiarities in concatenation between  central and peripheral cardiovascular changes under conditions of increasing fatigue. Research methods. Well-trained endurance runners underwent a 50 W increase in workload (bicycle ergometry) every 6 minutes and they exercised until inability to continue the task. Dynamics of concatenation between cardiac output and systolic arterial blood pressure (ABP), diastolic ABP and total peripheral resistance were assessed using a method based on matrix theory proposed by Lithuanian scientists. Research results. The increase of cardiac output during exercising has the same tendency of stepwise increase of workload, but changes of systolic and diastolic ABP with accumulation of fatigue could be characterized as linear type dependent with the time of exercising. The concatenation between the changes in cardiac performance and behaviour of peripheral vasculature increased at onset of exercising and the decrease or loss of the concatenation led up to inability to continue exercising. Discussion and conclusions. The importance of peripheral factors, i. e. decrease of diastolic blood pressure, reduction  of  total  peripheral  vascular  resistance  plays  an  increasingly  significant  role  for  cardiac  output  during continuous exercising. The concatenations between the changes of these indices and cardiac output increase and in the case of high-grade fatigue concatenations begin to decline. Keywords: cardiac output, periferal vascular resistance, concatenation.